Anti-Cult Movement and Religious Freedom for Religious Minorities in the Russian Arctic - Nadezhda Beliakova; Vera Kliueva (Religions, 2023)
In this article, using the example of the Russian Arctic, we analyze how the anti-cult movement creates the conditions for the discrimination and suppression of religious minorities. The anti-cultist (anti-sectarian) fears and phobias of the Russian establishment are closely bound to the fears of missionary activity. The change in legislation regulating missionary activity deliberately limits the activities of those religious communities, which, at the suggestion of the anti-cultists, are labeled in Russian society as “sectarian” and/or “foreign”.